2013
DOI: 10.1177/0193945913478844
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Aging Among Persons Living With Chronic Obstructive Pulmonary Disease

Abstract: Among pulmonary rehabilitation attendees, we explored their tendency to downplay versus acknowledge physical and psychosocial health limitations, and the subsequent impact either strategy had on how they perceive their own aging process. Participants (N = 87) were 44 to 82 years of age, and diagnosed with chronic obstructive pulmonary disease (COPD). The St. George's Respiratory Questionnaire measured their health limitations. The Attitudes to Aging Questionnaire captured their perspectives of aging. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 38 publications
1
13
1
Order By: Relevance
“…However, unlike our study, more negative perceptions of psychosocial loss were also reported in these studies. Our findings are more similar to a study with a broad age range of Canadians with COPD who expressed more negative physical change attitudes, but not psychosocial loss attitudes (Low et al , 2013). Most previous studies using the AAQ have focused on older populations and it could be argued that, in comparison, those in midlife generally maintain a range of social relationships through family, friends, and employment, and also have spent fewer years living with ill health.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, unlike our study, more negative perceptions of psychosocial loss were also reported in these studies. Our findings are more similar to a study with a broad age range of Canadians with COPD who expressed more negative physical change attitudes, but not psychosocial loss attitudes (Low et al , 2013). Most previous studies using the AAQ have focused on older populations and it could be argued that, in comparison, those in midlife generally maintain a range of social relationships through family, friends, and employment, and also have spent fewer years living with ill health.…”
Section: Discussionsupporting
confidence: 88%
“…Greater numbers of chronic health conditions have been linked to significantly more negative psychosocial loss and physical change attitudes toward aging (Kalfoss et al , 2010; Lucas-Carrasco et al , 2013). Specifically, individuals with functional limitations from COPD held more negative physical change attitudes, but minimized their symptoms in order to enjoy a greater quality of life in a sample aged 44 years and over (Low et al , 2013). Individuals aged 60 years and over with early dementia have reported more negative psychosocial loss scores than those without, particularly those with greater awareness of memory dysfunction (Trigg et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We conducted a secondary analysis of data collected in an earlier study of attitudes to aging among 87 PRP participants between the ages of 47 and 82 who were living with COPD [7].…”
Section: Methodsmentioning
confidence: 99%
“…In this way, limitations in physical functioning are seen as temporary and this circumvents negative affect. We tests the IPT using data collected in an earlier study of attitudes to aging among 87 pulmonary rehabilitation program (PRP) participants living with COPD at a variety of ages [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation